Concentric myocardial hypertrophy after one year of increased training volume in experienced distance runners - Venckunas, T.; Stasiulis, A.; Raugaliene, R. (British Journal of Sports Medicine, 2006)
Objectives: As evidence on the predominant type of cardiac hypertrophy due to endurance running training is inconsistent, the aim of this study was to investigate the effect of increased training volume on echocardiographic variables of distance runners. Methods: Twenty three adult, experienced, male distance runners underwent standard two dimensionally guided M mode and Doppler echocardiography before and after a one year period during which they were randomly allocated to either control (n = 11) or intervention (n = 12) groups. The intervention group increased their training volume from (mean (SD)) 8.0 (3.0) to 12.5 (3.9) hours/week without increasing the intensity, and the controls changed neither training parameter.